2000
DOI: 10.1093/brain/123.10.2077
|View full text |Cite
|
Sign up to set email alerts
|

Stride length regulation in Parkinson's disease: the use of extrinsic, visual cues

Abstract: It has been well documented that marked improvements in the hypokinetic gait pattern of Parkinson's disease patients are possible with the use of appropriate visual cues. This project served to evaluate Parkinson's disease gait performance as well as residual processing capacity while using fixed or gait-regulated visual cues. Three-dimensional kinematic, kinetic and electromyographic gait analysis was carried out on 14 patients and 14 matched controls in baseline conditions and with two types of visual cues: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
220
3
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 288 publications
(265 citation statements)
references
References 32 publications
21
220
3
9
Order By: Relevance
“…This finding is in agreement with other studies that have reported reduced ankle joint angular excursions of subjects with PD. 9,10 Most important, plantarflexion (but not dorsiflexion) was decreased in the PD group and consisted of a reduction in ROM during push-off and a reduction in plantarflexion at toe-off.…”
Section: Kinematicsmentioning
confidence: 98%
See 4 more Smart Citations
“…This finding is in agreement with other studies that have reported reduced ankle joint angular excursions of subjects with PD. 9,10 Most important, plantarflexion (but not dorsiflexion) was decreased in the PD group and consisted of a reduction in ROM during push-off and a reduction in plantarflexion at toe-off.…”
Section: Kinematicsmentioning
confidence: 98%
“…Lewis 10 observed marked variability in subjects with PD. The fairly small sample size would have contributed to this variability.…”
Section: Kineticsmentioning
confidence: 98%
See 3 more Smart Citations